Supersensitive CeOx-based nanocomposite sensor for the electrochemical detection of hydroxyl free radicals. Issue 9 (2nd March 2021) - Duanghathaipornsuk, Surachet; Kim, Dong-Shik; Phares, Tamara L.; Li, Cheng-Han; Jinschek, Joerg R.; Alba-Rubio, Ana C.
Abstract : An electrochemical sensor comprised of cerium oxide nanoclusters grafted to a highly conductive carbon provided a limit of detection of 0.6 μM ˙OH and successfully detected in vitro the presence of ˙OH in preosteoblast cells from mouse bone tissue. Abstract : It is well known that an excess of hydroxyl radicals (˙OH) in the human body is responsible for oxidative stress-related diseases. An understanding of the relationship between the concentration of ˙OH and those diseases could contribute to better diagnosis and prevention. Here we present a supersensitive nanosensor integrated with an electrochemical method to measure the concentration of ˙OH in vitro. The electrochemical sensor consists of a composite comprised of ultrasmall cerium oxide nanoclusters (<2 nm) grafted to a highly conductive carbon deposited on a screen-printed carbon electrode (SPCE). Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to analyze the interaction between cerium oxide nanoclusters and ˙OH. The CV results demonstrated that this electrochemical sensor had the capacity of detecting ˙OH with a high degree of accuracy and selectivity, achieving a consistent performance. Additionally, EIS results confirmed that our electrochemical sensor was able to differentiate ˙OH from hydrogen peroxide (H2 O2 ), which is another common reactive oxygen species (ROS) found in the human body. The limit of detection (LOD) observed with this electrochemical sensor was of 0.6 μM. Furthermore, this nanosized cerium oxide-based electrochemical sensor successfully detected in vitro the presence of ˙OH in preosteoblast cells from newborn mouse bone tissue. The supersensitive electrochemical sensor is expected to be beneficially used in multiple applications, including medical diagnosis, fuel–cell technology, and food and cosmetic industries.